Evaluation of the Implementation of Non-Cash Transactions at the Regional Secretariat of North Toraja District - Basri Rakhman; Winda Sosang; Indra Wijaya; Dedy Herianto (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Palu, 2024)
The implementation of non-cash transactions to date still has obstacles that hinder spending treasurers from carrying out their duties. The application only supports Sulselbar bank accounts so that other bank accounts take a long time for the fund transfer clearing process. Still constrained by a long and complicated procedure. Another obstacle to this factor is that the internet network, which often experiences disruption, will hamper the smooth process of Non-Cash Transactions. The objective of this research is to know and analyze the application of non-cash transactions at the Regional Secretariat of North Toraja Regency. This study used descriptive qualitative method. Data collection techniques are interviews, observation, and document review. The results showed that the application of non-cash transactions at the Regional Secretariat of North Toraja Regency has not been running optimally. In the aspect of transparency there is still minimal provision of information access facilities to the public. In the aspect of accountability, there is no standard operating procedure. In the aspect of efficiency, there are still minimal facilities and infrastructure and there are still several vacant positions. Meanwhile, on the effectiveness aspect, it has not been going well because the target to implement non-cash transactions as a whole for financial transactions has not been realized. Thus, the authors suggest that in the aspect of transparency, it is necessary to create a website as a means of public information related to financial management. In the aspect of accountability, it is necessary to make Standard Operating Procedures as a reference for implementation. In terms of efficiency, it is necessary to install an independent Teller Machine to facilitate transactions. In the aspect of effectiveness, it needs a commitment to implement it as a whole.